Intensive Word Problem Solving for Students With Learning Disabilities in Mathematics. (September 2022) - Witzel, Bradley; Myers, Jonté A.; Xin, Yan Ping
State exams frequently use word problems to measure mathematics performance, making difficulties with word problem solving a barrier for many students with learning disabilities (LD) in mathematics. Based on meta-analytic data for students with LD, five empirically validated word-problem strategies are presented, with components of model-based problem solving (MBPS) highlighted.